A method for preparing ultrathin lead iodide nanosheets and converting them into ultrathin perovskite nanosheets

By regulating factors such as solubility and temperature, ultra-thin lead iodide nanosheets were prepared by recrystallization, and chemical vapor deposition method was used to convert them into ultra-thin perovskite nanosheets, which solved the problem of preparing ultra-thin nanosheets in the prior art, and achieved efficient, controllable and low-cost nanosheet preparation.

CN115896915BActive Publication Date: 2025-04-18NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211353955.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2025-04-18
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

It is difficult to prepare large-area, uniform, ultra-thin two-dimensional lead iodide nanosheets and convert them into ultra-thin perovskite nanosheets, and the preparation method is complex, costly and poor controllability.

Method used

By regulating the difference in solubility and temperature of lead iodide, steam pressure, hydrophilicity of silicon substrates and droplet thickness during growth, ultrathin lead iodide nanosheets were prepared by recrystallization, and they were converted into ultrathin perovskite nanosheets by chemical vapor deposition.

Benefits of technology

Ultrathin lead iodide nanosheets with a size of 10 to 60 μm and a thickness of 2 to 4 nm were prepared, and converted into ultrathin perovskite nanosheets with a thickness of about 10 nm, which has the advantages of flexibility and universality, good controllability, good repeatability and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896915B_ABST
    Figure CN115896915B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing ultrathin lead iodide nanosheets and converting them into ultrathin perovskite nanosheets, the method is to uniformly mix pure lead iodide powder and ultrapure water in a certain proportion, heat and stir at a certain temperature to promote its dissolution, and then use a recrystallization method to drop a certain volume of solution on a silicon substrate, reduce the thickness of the droplet by a centrifuge, and then place it on a hot stage for crystallization to prepare ultrathin lead iodide nanosheets; then use chemical vapor deposition (CVD) to convert ultrathin lead iodide into ultrathin perovskite. The present invention can prepare ultrathin lead iodide nanosheets with a size of 10 to 60 μm, a thickness of 2 to 4 nm, a single crystal structure and high quality, and a perovskite nanosheet with a thickness of about 10 nm of the same size, which is a new method for the growth and preparation of ultrathin perovskite, and the growth method has the advantages of good controllability, high repeatability, high yield, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing ultrathin lead iodide nanosheets by a recrystallization method and ultrathin perovskite nanosheets by a chemical vapor deposition method with low cost, convenient operation and high repeatability, and belongs to the technical field of two-dimensional materials. Background Art

[0002] Metal iodides have attracted extensive attention from researchers due to their excellent electrical properties and potential application prospects. Among them, lead iodide has a wide energy band (Eg = 2.3 ~ 2.6eV), a high resistivity (ρ > 10 13 Ω·cm) and good chemical stability, and can be used as optoelectronic materials, room temperature radiation detectors and medical imaging materials. Compared with bulk materials, the unique two-dimensional conduction channels of low-dimensional layered materials give them the advantage of fast response speed. In order to explore the novel properties of two-dimensional materials, halide two-dimensional layered materials including lead iodide have been proven to be candidate materials for the preparation of excellent performance two-dimensional optoelectronic devices, so they have attracted the attention of a large number of research groups.

[0003] However, the preparation method of two-dimensional lead iodide nanosheets still needs to be further improved. At present, the methods for synthesizing lead iodide crystals with various nanosheet structures mainly include: mechanical exfoliation, physical vapor deposition and solution method. However, it is difficult to peel off a large area of ​​uniform thin layer material from the lead iodide prepared by mechanical exfoliation, and the repeatability is poor and the shape is irregular. The physical vapor deposition method can prepare lead iodide nanosheets with a smooth surface and regular shape, but the implementation of this method needs to be carried out under high temperature and vacuum environment, and the operation is relatively complicated and difficult to control. The conventional solution method for preparing lead iodide nanosheets also has a flat surface and regular shape, but the thickness of the grown nanosheets has not been well regulated, and it is difficult to prepare ultra-thin large-sized lead iodide nanosheets.

[0004] In addition, lead iodide is also one of the important precursors of perovskite. Lead iodide can react with amine iodides (such as methylammonium iodide (CH 3 NH 3 I,MAI)) react to form halide perovskites, such as CH 3 NH 3 PbI 3 (MAPI), these materials have remarkable optoelectronic properties and are used in devices such as high-efficiency perovskite solar cells (PSCs) and photodetectors.

[0005] The present invention comprehensively considers the difference between the solubility and temperature of lead iodide, the influence of vapor pressure, the thickness of the solution during recrystallization, the regulation of the hydrophilicity of the substrate and other factors, and proposes a method for preparing ultrathin lead iodide nanosheets and converting them into ultrathin perovskite nanosheets. The method is simple to prepare, low in cost, good in repeatability, high in yield, and can be easily promoted to industrial applications. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing ultrathin lead iodide nanosheets and converting them into ultrathin perovskite nanosheets in view of the deficiencies of the prior art. The present invention can prepare ultrathin lead iodide nanosheets with a size of 10 to 60 μm and a thickness of 2 to 4 nm, and the ultrathin lead iodide nanosheets can be prepared into perovskite nanosheets of the same size and a thickness of about 10 nm by chemical vapor deposition. At the same time, the provided method has the advantages of flexibility, universality, good controllability, good repeatability, and low cost. It is helpful for reference to the growth and preparation methods of other two-dimensional materials, and provides a two-dimensional material basis for devices such as photodetectors and memristors.

[0007] In order to solve the technical problem of the present invention, the technical solution proposed is: a method for preparing ultrathin lead iodide and converting it into ultrathin perovskite nanosheets, the method comprising the following steps

[0008] (1) mixing pure lead iodide powder with ultrapure water, heating and stirring, and obtaining an aqueous solution of lead iodide; the concentration of the lead iodide solution prepared by the pure lead iodide powder and ultrapure water is 0.0200-0.220 mol / L, the heating and stirring temperature is 30-90° C., the rotation speed is 100-400 rpm, and the stirring time is 1 h-72 h;

[0009] (2) placing the cleaned silicon substrate in a plasma cleaning machine for hydrophilic treatment, and then placing the silicon substrate on a coating machine, using a pipette to drop a lead iodide aqueous solution on the silicon substrate with a solution volume of 2 μL to 50 μL, using the centrifugal force of the coating machine to thin the surface liquid thickness, the coating machine speed is 1000 to 2000 rpm, the acceleration is 500 rpm, the duration is 5 to 10 s, and finally placing it on a hot stage at a constant temperature of 40° C. until the solution is completely evaporated to prepare an ultra-thin lead iodide nanosheet with a size of 10 to 60 μm and a thickness of 2 to 4 nm having a single crystal structure;

[0010] (3) placing the halide salt powder and the prepared ultrathin lead iodide nanosheets into a short glass tube with both ends open, and then placing the tube into a furnace tube of a dual-temperature zone CVD tube furnace, with the halide salt powder located at the center of the first temperature zone and the ultrathin lead iodide nanosheets located at the center of the second temperature zone; one end of the furnace tube close to the first temperature zone is connected to a gas pipeline, and the other end of the furnace tube is connected to a vacuum pump, and the mass of the halide salt powder used is 1 mg to 5 mg;

[0011] (4) Use a vacuum pump to evacuate the furnace tube to a vacuum degree of 10 -2 Pa~10 4 Pa, the furnace tube is cleaned three times with argon and evacuated to vacuum again, a hydrogen-argon mixed gas with a flow rate of 30 to 200 sccm is introduced into the furnace tube, and then the first temperature zone of the CVD tube furnace is heated to 180 to 190°C, and the second temperature zone is heated to 90°C. After keeping warm for 100 to 300 minutes, the vacuuming and heating are stopped, and the halide salt deposited on the silicon wafer reacts with the ultra-thin lead iodide to obtain an ultra-thin perovskite nanosheet with a size of 10 to 60 μm and a thickness of 10 nm.

[0012] Preferably, the gas introduced into the plasma cleaning in step (2) is oxygen (O 2 ), nitrogen (N 2 ) or air, the cleaning time is 30 to 600 seconds. ;

[0013] Preferably, the halide precursor in step (3) satisfies the general formula AX, wherein A is an alkylamine or aromatic amine or a metal ion, including methylamine (MA), formamidine (FA), phenethylamine (PEA), butylamine (BA) or naphthylmethylamine (NMA), and X is a halogen element, including chlorine (Cl), bromine (Br) or iodine (I).

[0014] Preferably, 10 mg of lead iodide particles are mixed with 10 ml of ultrapure water, and stirred on a heating table at a temperature of 90° C. and a rotation speed of 300 rpm for 6 h to obtain a lead iodide aqueous solution with a concentration of 0.0217 mol / L; then the silicon substrate is cut into 1 cm*1 cm sizes, cleaned, and then the substrate is placed in a plasma cleaning machine and O is introduced. 2 After a 300-second hydrophilic treatment, the hydrophilic treated substrate is placed on a glue spreader, and the glue spreader parameters are set to a speed of 1500 rpm, an acceleration of 500 rpm, and a duration of 5 s. A 20 μL lead iodide aqueous solution is then dropped onto the substrate using a pipette, and the glue spreader is started. After the glue spreader stops accelerating, the substrate is quickly transferred to a pre-prepared 40°C hot stage. After the solution is completely evaporated after standing still, lead iodide nanosheets with a size of 10 to 60 μm and a thickness of 2 to 4 nm can be prepared.

[0015] 3 mg of methylammonium iodide powder and two substrates with ultrathin lead iodide nanosheets were placed in a short glass tube wiped with alcohol, and then placed in the furnace tube of a dual-temperature zone CVD tube furnace, with the methylammonium iodide powder located in the center of the first temperature zone and the substrate located in the center of the second temperature zone; one end of the furnace tube close to the first temperature zone was connected to the gas pipeline, and the other end of the furnace tube was connected to the vacuum pump; the vacuum pump was turned on to evacuate the vacuum transfer equipment and the furnace tube, and the vacuum degree reached 10 -2When the furnace tube is cleaned, the vacuum degree of the furnace tube is pumped to 10 -2 Pa, and an argon-hydrogen mixture (Ar(90%) / H2O) was introduced into the tube furnace at a flow rate of 50 scc. 2 The evaporation zone was heated to 190°C within 45 min and maintained for 100 min, and the growth zone was heated to 90°C within 45 min and maintained for 200 min, so that the gas phase methyl iodide ammonium precursor reacted fully with the lead iodide nanosheets to obtain ultrathin MAPbI 3 Perovskite nanosheets.

[0016] The technical solution provided by the present invention is as follows: by adjusting the difference between the solubility and temperature of lead iodide, the vapor pressure, the hydrophilicity of the silicon substrate and the thickness of the droplet during growth, an ultrathin lead iodide nanosheet is prepared, and it is converted into an ultrathin perovskite nanosheet by chemical vapor deposition. The described preparation method has the advantages of flexibility, universality, good controllability, good repeatability and low cost. Specifically, it includes: (1) mixing pure lead iodide powder with ultrapure water, heating and stirring to obtain an aqueous solution of lead iodide; (2) cleaning the silicon substrate and placing it in a plasma cleaning machine for hydrophilic treatment. Then the substrate is placed on a sizing machine and dripped with the lead iodide aqueous solution, and the centrifugal force of the sizing machine is used to reduce the thickness of the droplet. After removing the silicon substrate, it is placed on a hot table at a constant temperature of 40°C until the solution is completely evaporated to prepare an ultrathin lead iodide nanosheet; (3) placing the ultrathin lead iodide nanosheet in a tubular furnace, and using chemical vapor deposition to convert it into an ultrathin perovskite nanosheet.

[0017] The concentration of the lead iodide supersaturated solution prepared by the pure lead iodide powder and ultrapure water is 0.0200-0.400 mol / L.

[0018] The heating and stirring temperature of the mixture of pure lead iodide and ultrapure water is 30-90° C., the rotating speed is 100-400 rpm, and the stirring time is 1h-72h.

[0019] The silicon substrate is cut to a size of 3 mm to 3 cm, and the gas introduced into the plasma cleaning is oxygen (O 2 ), nitrogen (N 2 ) or air, the cleaning time is 30-600s. The pipette drops a certain volume of lead iodide aqueous solution on the substrate, the solution volume is 2μL~50μL, the speed of the glue machine is 500~2000rpm, the acceleration is 500rpm, and the duration is 5~10s.

[0020] The mass of the halide salt powder used is 1 mg to 5 mg, and the halide precursor satisfies the general formula AX, wherein A is an alkylamine or ( / and) aromatic amine or ( / and) metal ion, including methylamine (MA), formamidine (FA), phenethylamine (PEA), butylamine (BA), naphthylmethylamine (NMA), and X is a halogen element, including chlorine (Cl), bromine (B), and iodine (I).

[0021] Beneficial Effects

[0022] The present invention discloses a method for preparing ultrathin lead iodide nanosheets and converting them into ultrathin perovskite nanosheets, comprising the following three parts: 1. obtaining a lead iodide solution by solution proportioning; 2. using a sizing machine to reduce the thickness of the droplet during recrystallization to obtain an ultrathin lead iodide nanosheet; 3. converting the obtained ultrathin lead iodide nanosheet into an ultrathin perovskite nanosheet by chemical vapor deposition. This method has important reference significance for growing more ultrathin nanosheets based on the solution method, and also provides a new idea for the growth and preparation of ultrathin perovskites.

[0023] The present invention can prepare ultra-thin large-size lead iodide nanosheets with a transfer size of 10 to 60 μm and a thickness of 2 to 4 nm, and can also prepare perovskite nanosheets with the same size and a thickness of about 10 nm. At the same time, the provided method has the advantages of flexibility, universality, good controllability, good repeatability, high yield, low cost, etc., and is relatively easy to promote to industrial applications.

[0024] In addition, the selection of substrate temperature and the speed of the coating machine also underwent a lot of experimental screening. In the process of the growth of lead iodide nanosheets, it was found that the growth size and thickness of lead iodide nanosheets were different for substrates with different temperatures. Among them, the substrate temperature of 40°C is most conducive to the growth of large-sized ultra-thin lead iodide nanosheets. The speed of the coating machine needs to be maintained at 1000-2000rpm. If the speed is too low, the effect of thinning the droplets cannot be achieved, and if it is too high, all the droplets will be thrown away.

[0025] Through a large number of experimental screenings, the thickness of the surface liquid is thinned by the centrifugal force of the glue machine. The speed of the glue machine is 1000-2000rpm, the acceleration is 500rpm, and the duration is 5-10s. It can be seen from Example 1 that if the thickness of the droplet is not regulated, it is difficult to grow and thin the lead iodide nanosheets. Most of the existing technical methods use different surfactants as additives to regulate the contact angle. Some technologies also use substrate modification to regulate the contact angle. In the present invention, the substrate is first plasma cleaned, and then a glue machine is used to remove excess solution with the help of centrifugal force, so that an ultra-thin layer of water film in contact with the substrate is retained, so as to regulate the size of the contact angle and make the material grow thinner.

[0026] Through a large number of experimental screenings, the mass of the halide salt powder used in step (3) is 1 mg to 5 mg. As shown in Comparative Example 2, excessive halide salt raw materials will cause the nanosheets to be corroded. It should be noted that both increasing the temperature and increasing the air flow rate will cause the halide salt atmosphere concentration to be locally too high, leading to similar results. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention. In the accompanying drawings:

[0028] Figure 1 It is a schematic diagram of realizing the preparation of ultra-thin lead iodide nanosheets by recrystallization method provided by the present invention;

[0029] Figure 2 It is a schematic diagram of realizing the conversion of ultra-thin lead iodide nanosheets into perovskite nanosheets provided by the present invention;

[0030] Figure 3 This is an optical photograph of the ultra-thin lead iodide nanosheet prepared by the present invention;

[0031] Figure 4 This is an atomic force microscope (AFM) image of the ultrathin lead iodide nanosheet prepared by the present invention;

[0032] Figure 5 Yes Figure 4 The height curve obtained by height scanning line analysis of the ultra-thin lead iodide nanosheet in the experiment;

[0033] Figure 6 This is the Raman spectrum of the ultra-thin lead iodide nanosheet prepared by the present invention;

[0034] Figure 7 The MAPbI prepared by the present invention is 3 Optical photograph of nanosheets;

[0035] Figure 8 The MAPbI prepared by the present invention is 3 Atomic force microscopy (AFM) images of nanosheets;

[0036] Fig. 9 Yes Figure 8 MAPbI prepared in 3 Height curve graph obtained by height scanning line analysis of nanosheets;

[0037] Fig.10 The MAPbI prepared by the present invention is 3 Photoluminescence (PL) spectra of nanosheets;

[0038] Fig.11 The FAPbI prepared by the present invention is 3 Photoluminescence (PL) spectrum of nanosheets, the inset is the FAPbI prepared by the present invention 3 Optical photograph of nanosheets;

[0039] Fig.12 The NMA prepared by the present invention is 2 PbI 4 Photoluminescence (PL) spectrum of nanosheets, the inset is the NMA prepared by the present invention 2 PbI 4 Optical photograph of nanosheets;

[0040] Fig.13 This is an optical photograph of lead iodide nanosheets grown without droplet thickness control;

[0041] Fig.14 Is it the addition of excess halide raw materials that leads to MAPbI 3 Optical photograph of the nanosheet being corroded; DETAILED DESCRIPTION

[0042] Embodiment 1:

[0043] 10 mg of lead iodide particles were mixed with 10 ml of ultrapure water and stirred on a heating table at 90 °C and 300 rpm for 6 h to obtain a lead iodide aqueous solution with a concentration of 0.0217 mol / L. The silicon substrate was cut into 1 cm*1 cm pieces and cleaned. The substrate was then placed in a plasma cleaner and O 2 After 300s of hydrophilic treatment, the hydrophilic treated substrate was placed on a glue machine, and the glue machine parameters were set to a speed of 1500rpm, an acceleration of 500rpm, and a duration of 5s. A 20μL lead iodide aqueous solution was then dropped onto the substrate using a pipette. The glue machine was started, and after the glue machine stopped accelerating, the substrate was quickly transferred to a 40°C hot table prepared in advance. After standing still, the solution evaporated completely, and lead iodide nanosheets with a size of 10 to 60μm and a thickness of 2 to 4nm were prepared. Figure 3 Optical images shown. Figure 4 and Figure 5 AFM data showed that its thickness is about 2nm.

[0044] Embodiment 2:

[0045] Place 3 mg of methylammonium iodide powder and two substrates with ultra-thin lead iodide nanosheets into a short glass tube wiped with alcohol, and then place it into the furnace tube of a dual-temperature zone CVD tube furnace. The methylammonium iodide powder is located in the center of the first temperature zone, and the substrate is located in the center of the second temperature zone. One end of the furnace tube close to the first temperature zone is connected to the gas pipeline, and the other end of the furnace tube is connected to the vacuum pump. Turn on the vacuum pump and evacuate the vacuum transfer equipment and furnace tube. When the vacuum degree reaches 10 -2 When the furnace tube is 1000 Pa, turn off the vacuum pump. Fill the furnace tube with pure argon gas to normal pressure, and then evacuate the furnace tube to achieve the purpose of cleaning the furnace tube. Repeat this operation three times. After the furnace tube is cleaned, evacuate the furnace tube to 10 -2 Pa, and an argon-hydrogen mixture (Ar(90%) / H2O) was introduced into the tube furnace at a flow rate of 50 scc. 2 The evaporation zone was heated to 190°C within 45 min and maintained for 100 min, and the growth zone was heated to 90°C within 45 min and maintained for 200 min, so that the gas phase methyl ammonium iodide precursor and the lead iodide nanosheets fully reacted to obtain ultrathin MAPbI 3 Perovskite nanosheets, whose optical morphology is as follows Figure 8 shown.

[0046] Embodiment 3:

[0047] Place 2 mg of methylammonium iodide powder and two substrates with ultra-thin lead iodide nanosheets into a short glass tube wiped with alcohol, and then place it into the furnace tube of a dual-temperature zone CVD tube furnace. The methylammonium iodide powder is located in the center of the first temperature zone, and the substrate is located in the center of the second temperature zone. One end of the furnace tube close to the first temperature zone is connected to the gas pipeline, and the other end of the furnace tube is connected to the vacuum pump. Turn on the vacuum pump and evacuate the vacuum transfer equipment and furnace tube. When the vacuum degree reaches 10 -2 When the furnace tube is 1000 Pa, turn off the vacuum pump. Fill the furnace tube with pure argon gas to normal pressure, and then evacuate the furnace tube to achieve the purpose of cleaning the furnace tube. Repeat this operation three times. After the furnace tube is cleaned, evacuate the furnace tube to 10 -2 Pa, and an argon-hydrogen mixture (Ar(90%) / H2O) was introduced into the tube furnace at a flow rate of 50 scc. 2 The evaporation zone was heated to 145°C within 45 min and maintained for 100 min, and the growth zone was heated to 90°C within 45 min and maintained for 200 min, so that the gas phase methyl iodide ammonium precursor and the lead iodide nanosheets fully reacted to obtain ultrathin FAPbI 3 Perovskite nanosheets, such as Fig.11 shown.

[0048] Embodiment 4:

[0049] Place 2 mg of naphthylmethylamine ammonium iodide powder and two substrates with ultra-thin lead iodide nanosheets into a short glass tube wiped with alcohol, and then place it into the furnace tube of a dual-temperature zone CVD tube furnace. The methylamine iodide powder is located in the center of the first temperature zone, and the substrate is located in the center of the second temperature zone. One end of the furnace tube close to the first temperature zone is connected to the gas pipeline, and the other end of the furnace tube is connected to the vacuum pump. Turn on the vacuum pump and evacuate the vacuum transfer equipment and furnace tube. When the vacuum degree reaches 10 -2 When the furnace tube is 1000 Pa, turn off the vacuum pump. Fill the furnace tube with pure argon gas to normal pressure, and then evacuate the furnace tube to achieve the purpose of cleaning the furnace tube. Repeat this operation three times. After the furnace tube is cleaned, evacuate the furnace tube to 10 -2 Pa, and an argon-hydrogen mixture (Ar(90%) / H2O) was introduced into the tube furnace at a flow rate of 50 scc. 2 The evaporation zone was heated to 145°C within 45 minutes and maintained for 100 minutes, and the growth zone was heated to 90°C within 45 minutes and maintained for 200 minutes, so that the gas phase methyl iodide ammonium precursor and the lead iodide nanosheets fully reacted to obtain ultrathin NMA 2 PbI 4 Perovskite nanosheets, such as Fig.12 shown.

[0050] Comparative Example 1:

[0051] 10 mg of lead iodide particles were mixed with 10 ml of ultrapure water and stirred on a heating table at 90 °C and 300 rpm for 6 h to obtain a lead iodide aqueous solution with a concentration of 0.0217 mol / L. The silicon substrate was cut into appropriate sizes and cleaned. The substrate was then placed in a plasma cleaner and O 2 After 300s of hydrophilic treatment, the substrate was transferred to a 40°C hot plate prepared in advance, and a 20 μL lead iodide aqueous solution was dropped onto the substrate using a pipette. After the solution evaporated completely, lead iodide nanosheets with a thickness of more than 20 nm were grown. Fig.13 shown.

[0052] Conclusion: It is difficult to grow lead iodide nanosheets thin without regulating the thickness of the droplets. Most of the existing technical methods use different surfactants as additives to regulate the contact angle. Some technologies also use substrate modification to regulate the contact angle. In the present invention, the substrate is first plasma cleaned, and then a gelling machine is used to remove excess solution with the help of centrifugal force, so that an ultra-thin layer of water film in contact with the substrate remains, thereby regulating the size of the contact angle and making the material grow thinner.

[0053] Comparative Example 2:

[0054] Place 6 mg of methylammonium iodide powder and two substrates with ultra-thin lead iodide nanosheets into a short glass tube wiped with alcohol, and then place it into the furnace tube of a dual-temperature zone CVD tube furnace. The methylammonium iodide powder is located in the center of the first temperature zone, and the substrate is located in the center of the second temperature zone. One end of the furnace tube close to the first temperature zone is connected to the gas pipeline, and the other end of the furnace tube is connected to the vacuum pump. Turn on the vacuum pump and evacuate the vacuum transfer equipment and furnace tube. When the vacuum degree reaches 10 -2 When the furnace tube is 1000 Pa, turn off the vacuum pump. Fill the furnace tube with pure argon gas to normal pressure, and then evacuate the furnace tube to achieve the purpose of cleaning the furnace tube. Repeat this operation three times. After the furnace tube is cleaned, evacuate the furnace tube to 10 -2 Pa, and an argon-hydrogen mixture (Ar(90%) / H2O) was introduced into the tube furnace at a flow rate of 50 scc. 2 The evaporation zone was heated to 190°C within 45 min and maintained for 100 min, and the growth zone was heated to 90°C within 45 min and maintained for 200 min, finally obtaining ultrathin MAPbI 3 Perovskite nanosheets can corrode, e.g. Fig.14 shown.

[0055] Conclusion: Excessive halide salt raw materials will cause the nanosheets to corrode. Here, the halide salt is excessive by adding raw materials. It should be noted that increasing the temperature and increasing the air flow rate will make the halide salt atmosphere concentration locally too high, leading to similar results.

[0056] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing ultrathin lead iodide and converting it into ultrathin perovskite nanosheets, characterized in that: The method comprises the following steps: 10 mg of lead iodide particles were mixed with 10 ml of ultrapure water, and stirred on a heating table at a temperature of 90 °C and a speed of 300 rpm for 6 h to obtain a lead iodide aqueous solution with a concentration of 0.0217 mol / L; the silicon substrate was then cut into 1 cm*1 cm in size and cleaned, and then the substrate was placed in a plasma cleaner and O2 was introduced for hydrophilic treatment for 300 s, and then the hydrophilic treated substrate was placed on a gelling machine, and the gelling machine parameters were set to a speed of 1500 rpm, an acceleration of 500 rpm, and a duration of 5 s, and then a pipette was used to drop a volume of 20 μL of lead iodide aqueous solution on the substrate; the gelling machine was started, and after the gelling machine stopped accelerating, the substrate was quickly transferred to a 40 °C hot table prepared in advance, and the solution was completely evaporated after standing still, and lead iodide nanosheets with a size of 10~60 μm and a thickness of 2 nm were prepared; 2 mg of methylammonium iodide powder and two substrates with ultrathin lead iodide nanosheets were placed in a short glass tube wiped with alcohol, and then placed in the furnace tube of a dual-temperature zone CVD tube furnace, with the methylammonium iodide powder located in the center of the first temperature zone and the substrate located in the center of the second temperature zone; one end of the furnace tube close to the first temperature zone was connected to the gas pipeline, and the other end of the furnace tube was connected to the vacuum pump; the vacuum pump was turned on to evacuate the vacuum transfer equipment and the furnace tube; when the vacuum degree reached 10 -2 When the furnace tube reaches 10 Pa, turn off the vacuum pump; pure argon gas is injected into the furnace tube to normal pressure, and then vacuum is evacuated to achieve the purpose of cleaning the furnace tube. This operation is repeated three times; after the furnace tube is cleaned, the vacuum degree of the furnace tube is evacuated to 10 -2 Pa, and an argon-hydrogen mixed gas is introduced into the tube furnace at a flow rate of 50 sccm; the evaporation zone is heated to 145 °C within 45 min and maintained for 100 min, and the growth zone is heated to 90 °C within 45 min and maintained for 200 min, so that the gas phase methyl iodide ammonium precursor and the lead iodide nanosheets can fully react to obtain ultrathin FAPbI3 perovskite nanosheets.

2. A method for preparing ultrathin lead iodide and converting it into ultrathin perovskite nanosheets, characterized in that: The method comprises the following steps: 10 mg of lead iodide particles were mixed with 10 ml of ultrapure water, and stirred on a heating table at a temperature of 90 °C and a speed of 300 rpm for 6 h to obtain a lead iodide aqueous solution with a concentration of 0.0217 mol / L; the silicon substrate was then cut into 1 cm*1 cm in size and cleaned, and then the substrate was placed in a plasma cleaner and O2 was introduced for 300 s of hydrophilic treatment, and then the hydrophilic treated substrate was placed on a glue machine, and the glue machine parameters were set to a speed of 1500 rpm, an acceleration of 500 rpm, and a duration of 5 s, and then a pipette was used to drop a volume of 20 μL of lead iodide aqueous solution on the substrate; the glue machine was started, and after the glue machine stopped accelerating, the substrate was quickly transferred to a 40 °C hot table prepared in advance. After standing still, the solution evaporated completely, and lead iodide nanosheets with a size of 10~60 μm and a thickness of 2 nm were prepared; 2 mg of naphthylmethylamine ammonium iodide powder and two substrates with ultrathin lead iodide nanosheets were placed in a short glass tube wiped with alcohol, and then placed in the furnace tube of a dual-temperature zone CVD tube furnace, with the methylamine iodide powder located in the center of the first temperature zone and the substrate located in the center of the second temperature zone; one end of the furnace tube close to the first temperature zone was connected to the gas pipeline, and the other end of the furnace tube was connected to the vacuum pump; the vacuum pump was turned on to evacuate the vacuum transfer equipment and the furnace tube; when the vacuum degree reached 10 -2 When the furnace tube reaches 10 Pa, turn off the vacuum pump; pure argon gas is injected into the furnace tube to normal pressure, and then vacuum is evacuated to achieve the purpose of cleaning the furnace tube. This operation is repeated three times; after the furnace tube is cleaned, the vacuum degree of the furnace tube is evacuated to 10 -2 Pa, and an argon-hydrogen mixed gas is introduced into the tube furnace at a flow rate of 50 sccm; the evaporation zone is heated to 145 °C within 45 min and maintained for 100 min, and the growth zone is heated to 90 °C within 45 min and maintained for 200 min, so that the gas phase methyl iodide ammonium precursor and the lead iodide nanosheets can fully react to obtain ultrathin NMA2PbI4 perovskite nanosheets.